Potent ovarian development as being stimulated by cocktail hormone in the female Scylla olivacea - Saetan, Jirawat; Duangprom, Supawadee; Songkoomkrong, Sineenart; Amonruttanapun, Prateep; Phanaksri, Teva; Surinlert, Piyaporn; Samhuay, Chompunut; Tamtin, Montakan; Suwansa-Ard, Saowaros; Cummins, Scott F.; Sobhon, Prasert; Kornthong, Napamanee (Frontiers in Marine Science, 2023)
The mud crab Scylla olivacea is widely cultured for its economic value, but reproduction issues limit its production. Vitellogenesis-inhibiting hormone (VIH), serotonin (5-HT), and gonadotropin-releasing hormone (GnRH) are important neurohormones that control reproduction in crustaceans. Mimicking crab hormone stimulation during reproduction has scarcely been reported. Comparison of the single hormone and multiple hormone approaches to crab hormonal control in S. olivacea is limited. In situ hybridization showed that injection of dsRNA-VIH could abolish its gene expression in neuronal clusters of female S. olivacea eyestalks, potentially reducing its inhibitory effects on ovarian maturation. This was confirmed by assessing the ovarian gonadosomatic index (GSI), hemolymph vitellogenin (Vg), an indicator of vitellogenesis, and gonad histology using dsRNA-VIH and 5-HT/GnRH combinations. Based on our findings, we demonstrated that administration of dsRNA-VIH significantly increased the gonadosomatic index (GSI) on days 14 and 28 post-treatment. The combination cocktail, however, consisting of 5-HT + GnRH + dsRNA-VIH on days 14 and 28, and GnRH + dsRNA-VIH on day 28, was the most efficacious in increasing GSI and enhancing crab ovarian maturation. Upregulation of hemolymph Vg levels was observed solely on the 28th day following treatment with dsRNA-VIH, 5-HT + GnRH + dsRNA-VIH, and GnRH + dsRNA-VIH. Differential gene expression analysis using quantitative RNA-sequencing of the neural tissues (brain and ventral nerve cord), revealed a significant upregulation of certain receptors (5-HTR, GnRHR, LHR, and FSHR), neuropeptides (sNPF, NPF1, NPF2, SIFamide, AKH/Crz, CHH, and RPCH), downstream reproductive-related genes (FAMeT, ESULT, progesterone-like protein), and prostanoid-related genes (phospholipase A and C, COX, Thromboxane A synthase, prostaglandin D, E, and F synthases) following treatment, particularly dsRNA-VIH + GnRH and/or 5-HT-injected individuals. Upregulation of prostaglandin E synthase and estrogen sulfotransferase genes was confirmed by real-time PCR. Since the construction and propagation of dsRNA-VIH is costly, its lower dose application supplemented with synthetic GnRH and/or 5-HT may be an alternative approach to ensure that female S. olivacea attain sufficient reproductive fecundity in aquaculture. Furthermore, we propose that the administration of multiple hormones in crabs may better emulate the physiological conditions of crustaceans in their natural habitat.